FISH MORTAUTY AND FISHING DURING AN UNPRECEDENTED DRAUGHT IN LAKE PICHHOLA, UDAIPUR - Durve, V S; Rajbanshi, V K (Indian Journal of Fisheries, 2011)
Lake Pichholft is the oldest lake in Udaipur city, reported to be in existence since the thirteenth century. It is named after the village Picfaholia then existing on its banla (Metoi 1969). The lake has a water spread of about 6.5 sq. km and an average deapth of about 6 m.